Pengaruh Daya Tarik Konten Instagram @Sahabatmarina terhadap Minat Audiens untuk Mengikuti Program Marina Beauty Journey - Judith Kenyatta Assaf; David Rizar Nugroho; Enden Darjatul Ulya; Mulyono Mulyono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The rapid development of digital technology has positioned social media, particularly Instagram, as a strategic channel for brands to conduct digital marketing and brand activation. This quantitative survey research aims to analyze the influence of Instagram content appeal (X) on the audience's interest in participating in the Marina Beauty Journey (Y) program. The study collected data from 100 female followers of the @sahabatmarina account, aged 15-25, who had been exposed to MBJ promotional content. Data analysis utilized simple linear regression. The descriptive analysis results showed that the appeal of @sahabatmarina’s content was perceived as Very High (Mean: 4.41), with Visual and Emotional indicators being the most dominant (Mean: 4.50), reflecting the effectiveness of aesthetic visuals and self-empowerment messaging. The audience's interest in joining the program was also categorized as Very High (Mean: 4.23), primarily demonstrated through the Interaction indicator (Mean: 4.33). The regression analysis confirmed a positive and significant influence of content appeal on audience interest, as indicated by a significance value of p<0.001 and a positive coefficient (beta = 0.622). The coefficient of determination (R2) indicated that content appeal contributed 41.0% to the formation of audience interest, while the remaining 59.0% was influenced by other external factors. In conclusion, the brand's digital content strategy, emphasizing strong visual and emotional connection, is highly effective in driving audience engagement and stimulating participation in its brand activation programs.